Construções de posse com clítico no PB : percurso diacrônico - Ev Angela Batista de Barros (2006)
Our goal in this research is to bring into evidence the diachronic way by which the frequency of the possessive clitic construction has declined in Brazilian Portuguese since the XVIIth century until now. This work investigates the structure and the properties of three possessive constructions the possessive pronoun, [a NPclitic] and [de NP] and the constraints on the possessive clitic extraction in PB. Based on the quantitative data exam, it is proposed a seven-steps diachronic reanalysis. The theoretical basis which supported this research was fundamentally the Minimalist Program (Chomsky 1993,1995). The quantitative methodology used for data analysis relied in the Variationist Theory proposed by Labov (1972,1994). The main objective is to provide a parametric account to a linguistic change that has made a genitive construction gradually replace a dative construction in BP.